Analysis of unexpected disruptive effects of contingent food reinforcement on automatically maintained self‐injury. Issue 1 (27th August 2021) - Rooker, Griffin W.; Hagopian, Louis P.; Haddock, Jennifer N.; Arevalo, Alexander R.; Bonner, Andrew C.; Dillon, Christopher M.
Abstract : Research has identified treatment‐responsive and treatment‐resistant subtypes of automatically maintained self‐injurious behavior (ASIB) based on patterns of responding in the functional analysis (FA) reflecting its sensitivity to disruption by alternative reinforcement, and the presence of self‐restraint. Rooker et al. (2019) unexpectedly observed reductions in treatment‐resistant self‐injury while participants performed an operant task. The current study further examined this in nine participants with treatment‐resistant ASIB in an example of discovery‐based research. An operant task engendering high rates of responding (switch‐pressing) to produce food, reduced self‐injury across all participants, and eliminated self‐injury for some participants under certain schedules. Although this finding must be replicated and evaluated over longer time periods, it provides some evidence that alternative reinforcement can disrupt self‐injury in these treatment‐resistant subtypes under some conditions. Reinforcer and response competition are discussed as possible mechanisms underlying these disruptive effects, as are the potential implications of these findings regarding treatment.